Concurrent measurement of dynamic changes in viral load, serum enzymes, T cell subsets, and cytokines in patients with severe fever with thrombocytopenia syndrome. - Jun Li; Yaping Han; Yiping Xing; Shuang Li; Lianhua Kong; Yongxiang Zhang; Lili Zhang; Ning Liu; Qian Wang; Shixia Wang; Shan Lu; Zuhu Huang (PLoS ONE, 2014)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infection caused by a novel Bunyavirus. Analysis on the dynamic changes of clinical, laboratory, and immunological abnormalities associated with SFTS in a concurrent study is lacking. Thirty-three SFTS patients were admitted to Jiangsu People's Hospital, Nanjing, China, and diagnosis was made based on the clinical symptoms and positive viral RNA detected by RT-PCR. Four patients deceased and twenty-nine survived. Blood samples were collected every other day between Day 5 and Day 15 from the onset of fever. Samples from healthy volunteers were used as normal controls. Peak viral RNA load, serum enzymes, IL-6, and IL-10 were significantly higher in deceased patients compared to survivors. Viral load, serum enzymes, and cytokines declined in survivors within 2 weeks from onset of fever. CD69+ T cells were elevated early after infection while HLA-DR+ and CTLA4+ T cells were elevated during the recovery phase of those who survived. High level SFTSV viral load was concurrently observed with reduced PLT, elevated serum enzymes, elevated pro-inflammatory and anti-inflammatory cytokines, and activation of CD69+ T cells. The degree and pattern of changes in these parameters may indicate the clinical outcome in SFTSV-infected patients.